Optimization of oil extraction from Pitanga (Eugenia Uniflora L) leaves using Simplex Centroid Design (SCD) - Araromi, Dauda O.; Alade, Abass Olanrewaju; Bello, Muibat Olabisi; Bakare, Taofiq; Akinwande, Bolanle Aishat; Jameel, Ahmad Tariq; Adegbola, Samuel A. (Taylor & Francis, 2017)
Simplex centroid design (SCD) was employed to optimize the mixing of petroleum ether, n-hexane, methanol and ethanol for the extraction of oil (PLO) from Pitanga (Eugenia uniflora L.) leaves, via Soxhlet extraction. The highest yield (54%) of Pitanga leaf oil (PLO) was obtained with 100% ethanol and the lowest yield (16%) from the mixture of methanol (33.3%)/hexane (33.3%)/ethanol (33.3%). The coefficient of determination (R2) of the model equation obtained was 0.91, while the adjusted R2 and predicted R2 were 0.8729 and 0.951, respectively. The saponification value (S.V.), iodine value, acid value and free fatty acid (FFA) are 35.34 mgKOH/g, 72.97 mgI2/g oil, 32.41 and 16.30 mgKOH/g, respectively.